The Identity of ’the Other’ in Gold Mountain Blue from the Perspective of Post-colonialism - Lin, Wanyi (Transactions on Social Science, Education and Humanities Research, 2024)
Zhang Ling is one of the new immigrant authors in China. The experience of living overseas and working as a hearing therapist gives her a profound understanding of Eastern and Western culture, which sets her apart from other immigrant writers. Gold Mountain Blue, published in 2009, describes the story of the fifth-generation immigrants from the Fang family and their survival situation in a foreign land, as well as their quest for identity. Using postcolonial theory and the methodology of close reading, this article takes several generations of Chinese immigrants in this novel as examples. Faced with unequal treatment from Western people, some Chinese immigrants find themselves marginalized and labeled as "the Other" in Western society, especially Chinese women who suffer from oppression based on both race and gender. Meanwhile, in the process of being othered, immigrants experience confusion about their identities. Based on the research above, this article proposes a new strategy for third-world groups to combat oppression from Western mainstream society, which includes fostering equal dialogue between cultures and embracing a sense of hybrid cultural identity. Furthermore, the author encourages minorities to reflect on their identities as well.